Compulsive exercise and weight suppression: Associations with eating pathology in distance runners. (January 2020) - Gorrell, Sasha; Scharmer, Christina; Kinasz, Kate; Anderson, Drew
Abstract: Some athletes, particularly those who participate in activities that emphasize leanness such as competitive running, are at greater risk for eating disorder (ED) pathology. Compulsive exercise (CE) is linked with ED pathology among female athletes, with evidence that CE for weight control is most strongly correlated with ED thoughts and behaviors. Weight suppression (WS), the discrepancy between highest adult weight and current weight, is also linked with ED symptoms. Taken together, runners with greater WS may be more likely to engage in CE to influence their weight or shape and may subsequently report other associated ED symptoms. As such, the current study investigated associations between CE and ED pathology in a mixed-gender sample of adult distance runners ( N  = 277, 51% female), and tested the impact of WS on this association. Results indicated that females reported greater CE and ED pathology, whereas males reported greater WS. A significant interaction effect for CE x WS, ( p  < .05) indicated that the relation between CE and ED scores was stronger among male runners who reported higher WS. In contrast, WS did not impact the association between CE and ED pathology for female runners. Results from the current study have important implications for the assessment and treatment of ED in athletes, specifically runners, and suggest that WS is an important factor to consider when working with male athletes. Highlights: Female runners reported greater compulsive exercise (CE) compared to males. Male runners reported lower eating disorder (ED) psychopathology than females. Male runners reported higher levels of weight suppression than females. Links between CE and ED scores were stronger in males with higher weight suppression. Weight history did not impact links between CE and ED pathology in females.